Hard carbon composite material as well as preparation method and application thereof

Through microwave-assisted chemical activation and coating treatment, hard carbon composite materials with porous and multi-closed pore structures are formed, which solves the problems of low sodium storage capacity and low first efficiency in sodium-ion batteries, and achieves high capacity and high first efficiency. Battery performance.

CN119361651APending Publication Date: 2025-01-24SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411548764.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing hard charcoal materials have problems with low sodium storage capacity and low first-term efficiency in sodium ion batteries, which are difficult to meet the needs of practical applications.

Method used

Through microwave -assisted chemical activation and covering, porous structures and multiple -closed structures are formed to improve sodium storage capacity and battery performance.

Benefits of technology

It significantly improves the sodium storage capacity and first effectiveness of hard charcoal composite materials, and is suitable for sodium ion batteries, which solves the problem of capacity and insufficient first effect in the existing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361651A_ABST
    Figure CN119361651A_ABST
Patent Text Reader

Abstract

The invention discloses a hard carbon composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: performing activating treatment and coating treatment on a mixture of asphalt and an alkaline reagent, thereby obtaining the modified asphalt, wherein the activating treatment mode is microwave activation; the microwave activation comprises a heating stage and a heat preservation stage; in microwave activation, the temperature of a heat preservation stage is 800-1000 DEG C, and the time of the heat preservation stage is 5-40 min; the coating treatment comprises a step of coating with a coating agent. Wherein the microwave-assisted chemical activation mode can greatly reduce the addition amount of an alkaline reagent and the activation time, and the obtained hard carbon composite material is rich in pore structures, especially has more closed pore structures, and can simultaneously ensure higher capacity and first effect when being practically applied to batteries (especially sodium ion batteries).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hard carbon composite material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries (LIBs) are of great significance in advanced energy storage systems due to their high energy density, long cycle life, and environmentally friendly properties. The growing demand for lithium-ion batteries in electronic devices and electric vehicles (EVs) has led to a gradual deepening of dependence on lithium resources. However, lithium resources in the earth's crust are limited. Therefore, in order to meet this challenge, people have turned their attention to sodium-ion batteries (SIBs). The structure of SIBs is basically the same as that of LIBs, and the preparation process is similar to that of lithium-ion batteries. Therefore, the difficulty of industrial implementation and promotion is relatively small. Despite this, SIB technology research is not thorough and is still in the early stages of industrialization. There are still some key links that need to be broken through. Among them, the development of SIB negative electrode materials is a prominent bottleneck problem.

[0003] At present, the research on sodium storage negative electrode materials mainly focuses on hard carbon materials, which have high reversible sodium storage capacity (can reach 300mAh / g and above, close to the lithium storage capacity of Li+ embedded in graphite negative electrode materials), low sodium storage potential (0V), abundant sources, low cost, high conductivity, low electrode potential, high safety, and good cycle performance and good thermal stability in electrolyte. However, they also have the problems of high cost and poor overall performance.

[0004] As one of the hard carbon materials, pitch-based carbon materials are a good choice. They have the advantages of low cost, excellent conductivity and high carbon content, and are considered to be promising negative electrode materials. However, the direct pyrolysis of pitch-based hard carbon through uncontrolled liquid phase carbonization forms a microstructure with small interlayer spacing and high orientation, resulting in low sodium storage capacity and low initial efficiency of the resulting battery.

[0005] Therefore, there is an urgent need for a hard carbon composite material that has both high capacity and high initial efficiency for practical applications. Summary of the invention

[0006] In order to overcome the above defects of the hard carbon materials in the prior art, the present invention provides a hard carbon composite material and a preparation method and application thereof. When the hard carbon material is actually applied to batteries (especially sodium ion batteries), it can simultaneously ensure high capacity and initial efficiency.

[0007] To achieve the above purpose, the present invention adopts the following technical solution.

[0008] The present invention provides a method for preparing a hard carbon composite material, which comprises the following steps:

[0009] The mixture of asphalt and alkaline reagent is subjected to activation treatment and coating treatment to obtain the product; wherein,

[0010] The activation treatment method is microwave activation; the microwave activation includes a heating stage and a heat preservation stage; in the microwave activation, the temperature of the heat preservation stage is 800°C-1000°C, and the time of the heat preservation stage is 5-40min;

[0011] The coating process includes the step of coating with a coating agent.

[0012] In the present invention, the alkaline reagent can chemically activate the asphalt, mainly to form pores, and to regulate the pores to a certain extent; further assisted by microwave activation under specific conditions, the intercalation effect between microwaves and chemical reagents is maximized, forming as many new pores as possible or widening existing pores as much as possible, and then coating to form more closed pores, thereby increasing the sodium storage capacity. Compared with conventional chemical activation, the use of microwave activation assistance can greatly reduce the amount of alkaline reagent added and the activation time, which is more friendly to equipment and the environment.

[0013] In some embodiments, during the microwave activation, the temperature of the insulation stage is 900°C.

[0014] In some embodiments, during the microwave activation, the insulation stage lasts for 30 minutes.

[0015] In some embodiments, in the microwave activation, the frequency of the insulation stage is 18000-22000 Hz, preferably 20000 Hz.

[0016] In some embodiments, during the microwave activation, the power of the insulation stage is 30 KW.

[0017] In some embodiments, during the microwave activation, the heating rate in the heating stage is 10-50°C / min, preferably 35°C / min.

[0018] In some embodiments, the microwave activation process is performed in a microwave oven.

[0019] In some embodiments, the microwave activation process is performed under an inert gas.

[0020] Wherein, the inert gas is preferably nitrogen and / or argon.

[0021] The flow rate of the inert gas is preferably 0.1-5 L / min, more preferably 0.5 L / min.

[0022] In some embodiments, the softening point of the asphalt is 100-400°C, such as 300°C.

[0023] In some embodiments, the asphalt includes petroleum asphalt and / or coal tar asphalt, preferably petroleum asphalt, and more preferably isotropic petroleum asphalt.

[0024] In some embodiments, the asphalt is in the form of asphalt pellets.

[0025] Wherein, the asphalt particles are preferably obtained by a crushing device; the crushing device is preferably one or more of a jet mill, a roller mill, a sand mill or a ball mill.

[0026] The particle size of the asphalt particles is preferably 3-8 μm, more preferably 5 μm.

[0027] In some embodiments, the alkaline agent includes a weak base agent and / or a strong base agent.

[0028] In some embodiments, the alkaline agent is a weak base agent. Generally, when chemical activation is performed, the activation effect of a strong base agent is often stronger than that of a weak base agent. However, in some embodiments of the present invention, when a weak base agent is used for activation, in combination with other parameters, an activation effect equivalent to or better than that of a strong base agent is unexpectedly achieved, and defects such as equipment corrosion caused by a strong base agent, excessive activation and difficulty in coating, etc. are avoided.

[0029] In some embodiments, the alkaline agent is a potassium salt and / or a sodium salt, preferably an organic salt and / or an inorganic salt of potassium and / or sodium, more preferably one or more selected from potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium formate, potassium oxalate, sodium formate and sodium oxalate, and further more preferably potassium formate.

[0030] In some embodiments, the mass ratio of the asphalt to the alkaline agent is 1:0.05-1:2, preferably 1:0.3.

[0031] In some embodiments, the preparation of the mixture includes the step of mixing the asphalt and the alkaline agent in a mixing device.

[0032] Wherein, the mixing equipment is preferably a V-shaped mixer, a cone mixer or a stirring mixer.

[0033] In some embodiments, the coating agent is asphalt and / or resin.

[0034] In some embodiments, the softening point of the coating agent is 80-150°C, preferably 110°C.

[0035] In some embodiments, the coking value of the coating agent is 10-40%, preferably 25%.

[0036] In the present invention, the amount of the coating agent can be adjusted according to the residual carbon value in the hard carbon composite material finally obtained; the residual carbon value means the residual amount of the coating agent after the coating treatment, that is, the content of the coating layer in the hard carbon composite material. Those skilled in the art can know its specific meaning. Specifically, the residual amount of the coating agent is preferably 0.1-5%, more preferably 3%.

[0037] In some embodiments, the coating treatment comprises the steps of mixing the product obtained by the activation treatment with a coating agent and heating the mixture for reaction.

[0038] The temperature of the heating reaction is preferably 800-1600°C, more preferably 1300°C.

[0039] Wherein, the heating rate of the heating reaction is preferably 1-15°C / min, more preferably 5°C / min.

[0040] Wherein, the insulation time of the heating reaction is preferably 1-6h, more preferably 2h.

[0041] In some embodiments, washing and drying steps are further included between the activation treatment and the coating treatment.

[0042] Wherein, the washing process is preferably carried out in a washing device; the washing device is preferably one of a centrifuge, a plate and frame filter, a filter press, a positive pressure filter or a membrane separator, and more preferably a filter press.

[0043] Wherein, the washing reagent is preferably water.

[0044] The present invention also provides a hard carbon composite material, which comprises a core and a coating layer; wherein:

[0045] The inner core is porous hard carbon;

[0046] The coating layer is amorphous carbon;

[0047] The pore size range of the hard carbon composite material is 0.2-1 nm; wherein the proportion of pores with a pore size less than 0.7 nm is not less than 80%; the proportion is the pore volume proportion based on the total pore volume;

[0048] The cumulative pore volume of the pores in the hard carbon composite material is 0.01-0.06 cm 3 / g.

[0049] In the present invention, the porous hard carbon may be obtained from asphalt, which may be as defined above.

[0050] In the present invention, the pore size range refers to the pore size distribution of the pores in the hard carbon composite material, that is, the pores in the hard carbon composite material are not distributed with equal pore sizes.

[0051] In some embodiments, the proportion of pores with a pore size below 0.7 nm in the hard carbon composite material is greater than 85, for example 86.46%; the proportion is the pore volume proportion based on the total pore volume.

[0052] In some embodiments, the cumulative pore volume of the pores in the hard carbon composite material is 0.04-0.06 cm 3 / g, for example 0.052cm 3 / g.

[0053] In some embodiments, the pores in the hard carbon composite material have pore sizes ranging from 0.3-0.4 nm, 0.5-0.7 nm, and 0.7-0.9 nm.

[0054] The proportion of pores with a pore diameter of 0.3-0.4 nm is preferably 20-30%, for example 23.75%; the proportion is the pore volume proportion based on the total pore volume.

[0055] The proportion of pores with a pore diameter of 0.5-0.7 nm is preferably 60-70%, for example 62.70%; the proportion is the pore volume proportion based on the total pore volume.

[0056] Among them, the proportion of pores with a pore diameter of 0.7-0.9 nm is preferably 10-20%, for example 13.55%; the proportion is the pore volume proportion based on the total pore volume.

[0057] In some embodiments, the mass content of the coating layer is 0.1-5%, preferably 3%.

[0058] In some embodiments, the hard carbon composite material has a specific surface area of ​​2-4 m 2 / g, for example 2.4m 2 / g, 2.6m 2 / g, 2.8m 2 / g or 3.1m 2 / g.

[0059] The present invention also provides a hard carbon composite material, which is prepared by the preparation method of the hard carbon composite material as described above.

[0060] In the present invention, the hard carbon composite material is as defined above.

[0061] The present invention also provides an application of the hard carbon composite material as described above in a sodium ion battery.

[0062] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0063] The reagents and raw materials used in the present invention are commercially available.

[0064] The positive and progressive effects of the present invention are:

[0065] The present invention uses the strategy of microwave-assisted chemical activation and coating, and utilizes the intercalation effect between microwaves and chemical reagents to form new pores in the inner core or widen existing pores, and then coats to form more closed pores, thereby increasing the sodium storage capacity of the obtained hard carbon composite material. The porous structure contained in the hard carbon composite material, especially the multi-closed pore structure formed after coating, successfully overcomes the inherent shortcomings of existing asphalt materials, and when actually applied to batteries (especially sodium ion batteries), its capacity and initial efficiency are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 It is the pore size distribution diagram of the hard carbon composite material of Example 1, Comparative Example 1, Comparative Example 3 and Comparative Example 4 in the effect embodiment.

[0067] Figure 2 This is a graph showing the cumulative pore volume results of the hard carbon composite materials of Example 1, Comparative Example 1, Comparative Example 3 and Comparative Example 4 in the effect examples.

[0068] Figure 3 It is a charge and discharge curve diagram of the battery obtained from the hard carbon composite material of Example 1 in the effect embodiment. DETAILED DESCRIPTION

[0069] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0070] In the following examples and comparative examples, the specific information of each raw material is as follows:

[0071] 1. Raw materials: petroleum asphalt (softening point at 300℃, isotropic, commercially available);

[0072] 2. Coating agent: asphalt (softening point: 110°C, coking value: 25%, any commercially available one), resin (liquid resin, coking value: 40%, any commercially available one).

[0073] Example 1

[0074] The hard carbon composite material of this embodiment is prepared by the following steps:

[0075] S1.Use isotropic petroleum asphalt with softening point at 300℃ as raw material, grind it by air flow mill (i.e. air flow mill) to control the particle size to 5um.

[0076] S2. Physically mix the crushed asphalt and potassium formate in a mass ratio of 1:0.3 (V-type mixer), and then put the evenly mixed materials into a microwave heating furnace for activation treatment. The nitrogen flow rate is 0.5L / min, the heating rate is 35℃ / min, the insulation temperature is 900℃, the insulation time is 30min, and the microwave heating frequency is 20000Hz.

[0077] S3. The activated material is washed with water in a filter press until it is neutral, dried, and then mixed with asphalt (the amount is 3% based on the residual carbon content after carbonization).

[0078] S4. The mixed material is subjected to high-temperature carbonization at a carbonization temperature of 1300°C, a heating rate of 5°C / min, and a heat preservation time of 2h. After cooling, a hard carbon composite material can be obtained.

[0079] Example 2

[0080] Referring to the conditions of Example 1, steps S1, S2 and S4 are kept the same as in Example 1, and only step S3 is changed as follows:

[0081] S3. The activated asphalt material is washed with water in a filter press until it is neutral, dried and then mixed with resin (the amount is 3% based on the residual carbon content after carbonization).

[0082] Example 3

[0083] Referring to the conditions of Example 1, steps S1, S3 and S4 are kept the same as in Example 1, and only step S2 is changed as follows:

[0084] S2. Physically mix the crushed asphalt and potassium oxalate in a mass ratio of 1:0.3 (V-type mixer), and then put the evenly mixed materials into a microwave heating furnace for activation treatment. The nitrogen flow rate is 0.5L / min, the heating rate is 35℃ / min, the insulation temperature is 900℃, the insulation time is 30min, and the microwave heating frequency is 20000Hz.

[0085] Example 4

[0086] Referring to the conditions of Example 1, steps S1, S3 and S4 are kept the same as in Example 1, and only step S2 is changed as follows:

[0087] S2. Physically mix the crushed asphalt and potassium hydroxide in a mass ratio of 1:0.3 (V-type mixer), and then put the evenly mixed materials into a microwave heating furnace for activation treatment. The nitrogen flow rate is 0.5L / min, the heating rate is 35℃ / min, the insulation temperature is 900℃, the insulation time is 30min, and the microwave heating frequency is 20000Hz.

[0088] Comparative Example 1

[0089] Referring to the conditions of Example 1, keep step S1 the same as in Example 1, and change step S2 as follows:

[0090] S2. The crushed asphalt material is directly carbonized at a temperature of 1300°C and a heating rate of 5°C / min; the insulation time is 2h.

[0091] After cooling, a hard carbon composite material can be obtained.

[0092] Comparative Example 2

[0093] Referring to the conditions of Example 1, steps S1 and S2 are kept the same as in Example 1, and step S3 is changed as follows:

[0094] S3. Wash the activated asphalt material in a filter press until it is neutral, and then dry it; directly carry out carbonization at a temperature of 1300°C and a heating rate of 5°C / min; and keep it warm for 2h.

[0095] After cooling, a hard carbon composite material can be obtained.

[0096] Comparative Example 3

[0097] Referring to the conditions of Example 1, steps S1, S3 and S4 are kept the same as in Example 1, and only step S2 is changed as follows:

[0098] S2. The crushed asphalt is directly put into a microwave heating furnace for activation treatment, with a nitrogen flow rate of 0.5 L / min, a heating rate of 35°C / min, a holding temperature of 900°C, a holding time of 30 min, and a microwave heating frequency of 20,000 Hz.

[0099] Comparative Example 4

[0100] Referring to the conditions of Example 1, steps S1, S3 and S4 are kept the same as in Example 1, and only step S2 is changed as follows:

[0101] S2. After the crushed asphalt and potassium formate are mixed evenly in a mass ratio of 1:0.3, they are put into a conventional heating furnace for activation treatment. The nitrogen flow rate is 0.5L / min, the heating rate is 2℃ / min, the insulation temperature is 900℃, and the insulation time is 30min.

[0102] Comparative Example 5

[0103] Referring to the conditions of Example 1, steps S1, S3 and S4 are kept the same as in Example 1, and only step S2 is changed as follows:

[0104] S2. Physically mix the crushed asphalt and potassium formate in a mass ratio of 1:0.3 (V-type mixer), and then put the evenly mixed materials into a microwave heating furnace for activation treatment. The nitrogen flow rate is 0.5L / min, the heating rate is 35℃ / min, the insulation temperature is 900℃, the insulation time is 60min, and the microwave heating frequency is 20000Hz.

[0105] Effect Example

[0106] The hard carbon composite materials obtained in Examples 1-4 and Comparative Examples 1-5 were characterized as follows:

[0107] (1) Specific surface area and pore structure characterization

[0108] The test was carried out using an American Micromeritics ASAP 2460 V2.01 fully automatic adsorption and desorption instrument. The adsorbent for the hard carbon composite material was nitrogen, the measurement temperature was 77K, and the specific surface area was calculated by the BET method. The adsorbent for the hard carbon composite material was carbon dioxide, the measurement temperature was 273K, and the pore structure was obtained by the HS-2D-NLDFT model.

[0109] The specific characterization results are shown in Table 1. Figure 1 and Figure 2 As shown, Figure 1 and Figure 2 The pore structure distribution diagrams and cumulative pore volume result diagrams of the hard carbon composite materials obtained in Example 1, Comparative Example 1, Comparative Example 3 and Comparative Example 4 are respectively.

[0110] Depend on Figure 1 and Figure 2 The pore size distribution and cumulative pore volume results shown show that the hard carbon composite material of Example 1 has a pore size of 86.46% (the proportion is the pore volume proportion based on the total pore volume), while the proportions of Comparative Examples 1, 3 and 4 are 68.87%, 70.39% and 100% respectively, and the cumulative pore volume of Example 1 is 0.052cm 3 / g, which is significantly higher than that of Comparative Examples 1, 3 and 4.

[0111] Specifically, the hard carbon composite material of Example 1 has pore size ranges including 0.3-0.4 nm, 0.5-0.7 nm and 0.7-0.9 nm, corresponding to proportions of 23.75%, 62.70% and 13.55%, respectively.

[0112] (2) Electrochemical performance test

[0113] The hard carbon composite materials obtained in Examples 1-4 and Comparative Examples 1-5 were mixed with the binder polyvinylidene fluoride PVDF and the conductive agent Super-P in a mass ratio of 90:5:5, and N-methylpyrrolidone NMP was added as a dispersant to prepare a slurry. The mixed slurry was then evenly coated on the current collector copper foil. After drying, the pole piece was punched into a pole piece with a diameter of 12 mm, and the pole piece was dried at 120°C for 5 hours under vacuum conditions, and then transferred to an argon glove box for standby use. The assembly of the half-cell was carried out in a glove box with an argon atmosphere, with metallic sodium as the counter electrode and 1M NaPF6 solution as the electrolyte, wherein the NaPF6 solution solvent was ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, and glass fiber filter paper was used as a diaphragm to assemble a CR2032 button cell.

[0114] The charge and discharge tests were conducted under constant current charge and discharge conditions at current densities of C / 10 and C / 50. The tests were conducted under the conditions of a discharge cut-off voltage of 0V and a charge cut-off voltage of 2V.

[0115] The test results are shown in Table 1 and Figure 3 .

[0116] Table 1

[0117]

[0118] From Table 1 and Figure 3 The results show that when the hard carbon composite material of the present invention is applied to sodium ion batteries, the specific capacity is above 350 mAh / g, the first efficiency is above 87%, the platform capacity ratio is above 71%, and the specific surface area after coating is above 4 m 2 / g or less.

[0119] In Comparative Example 1, when microwave-assisted chemical activation and coating were not involved, the specific capacity, first effect, platform capacity ratio and specific surface area all changed; among them, the decrease in specific capacity and platform capacity ratio was particularly obvious.

[0120] In Comparative Example 2, even after microwave-assisted chemical activation, without coating, the specific capacity, first effect, platform capacity ratio and specific surface area all changed; among them, the changes in first effect and specific surface area were particularly obvious.

[0121] In Comparative Examples 3 and 4, even though the coating was performed, microwave activation or chemical activation alone failed to significantly improve the specific capacity and platform capacity ratio of the obtained battery.

[0122] In Comparative Example 5, the activation time was adjusted, and the specific surface area of ​​the sample after coating was larger, making it difficult to coat, and the specific capacity, first effect, and platform capacity ratio were all significantly reduced; indicating that effective closed pores could not be formed and the platform sodium storage capacity could not be effectively increased.

[0123] In summary, the above results show that the hard carbon composite material of the present invention, the microwave-assisted chemical activation process exhibits a synergistic activation effect; wherein, the intercalation effect produced between microwaves and chemical reagents forms new pores or widens existing pores, thereby producing carbon with higher porosity; it helps to create more open pores to form more closed pores through coating, thereby increasing the sodium storage capacity; at the same time, it helps to increase the diffusion rate of sodium ions and improve the reaction kinetics; at the same time, this method also greatly reduces the amount of alkaline reagent added and the activation time.

Claims

1. A method for preparing a hard carbon composite material, characterized in that: The preparation method of the hard carbon composite material comprises the following steps: The mixture of asphalt and alkaline reagent is activated and coated to obtain: The activation treatment method is microwave activation; the microwave activation includes a heating stage and a heat preservation stage; in the microwave activation, the temperature of the heat preservation stage is 800°C-1000°C, and the time of the heat preservation stage is 5-40min; The coating process includes the step of coating with a coating agent.

2. The method for preparing the hard carbon composite material according to claim 1, characterized in that: In the microwave activation, the temperature of the insulation stage is 900°C; And / or, in the microwave activation, the insulation stage lasts for 30 minutes; And / or, the alkaline reagent includes a weak base reagent and / or a strong base reagent; and / or, the alkaline agent is a potassium salt and / or a sodium salt, preferably an organic salt and / or an inorganic salt of potassium and / or sodium, more preferably one or more selected from potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium formate, potassium oxalate, sodium formate and sodium oxalate, and further more preferably potassium formate; And / or, the mass ratio of the asphalt to the alkaline agent is 1:0.05-1:2, preferably 1:0.

3.

3. The method for preparing the hard carbon composite material according to claim 1, characterized in that: The softening point of the asphalt is 100-400°C, for example 300°C; And / or, the asphalt comprises petroleum asphalt and / or coal tar asphalt, preferably petroleum asphalt, more preferably isotropic petroleum asphalt; And / or, the asphalt exists in the form of asphalt particles; wherein the particle size of the asphalt particles is preferably 3-8 μm, more preferably 5 μm.

4. The method for preparing the hard carbon composite material according to claim 1, characterized in that: In the microwave activation, the frequency of the insulation stage is 18000-22000 Hz, preferably 20000 Hz; And / or, in the microwave activation, the power of the heat preservation stage is 30KW; And / or, in the microwave activation, the heating rate in the heating stage is 10-50°C / min, preferably 35°C / min; And / or, the microwave activation process is carried out in a microwave oven; And / or, the microwave activation process is carried out in an inert gas; Wherein, the inert gas is preferably nitrogen and / or argon; The flow rate of the inert gas is preferably 0.1-5 L / min, more preferably 0.5 L / min.

5. The method for preparing the hard carbon composite material according to claim 1, characterized in that: The coating agent is asphalt and / or resin; and / or, the softening point of the coating agent is 80-150° C., preferably 110° C.; And / or, the coking value of the coating agent is 10-40%, preferably 25%.

6. The method for preparing the hard carbon composite material according to claim 1, characterized in that: The preparation of the mixture includes the steps of mixing the asphalt and the alkaline agent in a mixing device; Wherein, the mixing equipment is preferably a V-shaped mixer, a cone mixer or a stirring mixer; And / or, the coating treatment includes the steps of mixing the product obtained by the activation treatment with the coating agent and heating the mixture for reaction; Wherein, the temperature of the heating reaction is preferably 800-1600°C, more preferably 1300°C; Wherein, the heating rate of the heating reaction is preferably 1-15°C / min, more preferably 5°C / min; The holding time of the heating reaction is preferably 1-6 hours, more preferably 2 hours; And / or, washing and drying steps are further included between the activation treatment and the coating treatment.

7. A hard carbon composite material, characterized in that: The hard carbon composite material comprises a core and a coating layer; wherein, The inner core is porous hard carbon; The coating layer is amorphous carbon; The pore size range of the hard carbon composite material is 0.2-1 nm; wherein the proportion of pores with a pore size less than 0.7 nm is not less than 80%; the proportion is the pore volume proportion based on the total pore volume; The cumulative pore volume of the pores in the hard carbon composite material is 0.01-0.06 cm 3 / g.

8. The hard carbon composite material according to claim 7, characterized in that: The proportion of pores with a pore diameter of less than 0.7 nm in the hard carbon composite material is greater than 85, for example, 86.46%; the proportion is the pore volume proportion based on the total pore volume; And / or, the cumulative pore volume of the pores in the hard carbon composite material is 0.04-0.06cm 3 / g, for example 0.052cm 3 / g; and / or, the pores in the hard carbon composite material have pore sizes ranging from 0.3-0.4 nm, 0.5-0.7 nm and 0.7-0.9 nm; Among them, the proportion of pores with a pore diameter of 0.3-0.4 nm is preferably 20-30%, for example 23.75%; the proportion is the pore volume proportion based on the total pore volume; Among them, the proportion of pores with a pore diameter of 0.5-0.7 nm is preferably 60-70%, for example 62.70%; the proportion is the pore volume proportion based on the total pore volume; Among them, the proportion of pores with a pore diameter of 0.7-0.9 nm is preferably 10-20%, for example 13.55%; the proportion is the pore volume proportion based on the total pore volume; And / or, the mass content of the coating layer is 0.1-5%, preferably 3%; And / or, the specific surface area of ​​the hard carbon composite material is 2-4m 2 / g, for example 2.4m 2 / g, 2.6m 2 / g, 2.8m 2 / g or 3.1m 2 / g.

9. A hard carbon composite material, characterized in that: The hard carbon composite material is prepared by the preparation method of the hard carbon composite material according to any one of claims 1 to 6.

10. Use of the hard carbon composite material according to any one of claims 7 to 9 in a sodium ion battery.